Impact of the medicine Hydroxyurea on reproduction and development, using Drosophila melanogaster as a model organism - Rangel, Veronica Ferreira [UNESP]; Patarro, Thais de França [UNESP]; Manzato, Antonio José [UNESP]; Bicudo, Hermione Elly Melara de Campos [UNESP] (Bentham Science Publishers, 2014)
The clinical efficacy of oral hydroxyurea (HU) in the treatment of the sickle cell disease (SCD) is already proven. However, side-effects on reproduction and development still cause concerns, mainly in long term treatments. We used Drosophila melanogaster as a model organism in the study of this subject. This species has been considered favorable for studying human diseases and responses to drugs because both organisms share more than 50% of the genes for disease and exhibit a very similar drug metabolism. In addition, D. melanogaster allows laboratory approaches that are not possible in humans. We analyzed the impact of the concentrations HU 0.1 and HU 0.25 on productivity, oviposition rate, emergence period duration, mortality and development time from egg to adult. HU affected all these traits, showing dose dependence. The frequency of mating, and duration of premating and mating times of flies were also analyzed in treatments with HU 0.25. Considering all the traits, the treatments decreased the productivity, oviposition rate and frequency of mating, and increased the emergence period duration, mortality rate from egg to adult and development time. The premating and mating times duration were affected in a more complex way. On the basis of the knowledge that HU affects DNA synthesis and repair, and other data available in the literature, we raised hypotheses to explain the present observations. The results and hypotheses suggested new approaches for further studies of particular and important aspects. In general, this study reinforces the validity of the concern with HU side-effects.
Keywords: Emergence period duration; impaired effect of hydroxyurea; mortality from egg to adult; number of progeny; oviposition rate